Aortic Stenosis Associated with an Increase in Mortality in Surgical Hip Fracture Patients. Issue 1 (January 2023) - Fouda, Eslam A.; Chaves-Cardona, Harold E.; Renew, J. Ross; Spaulding, Aaron C.; Porter, Steven B.
Abstract : Aortic stenosis is not an uncommon comorbidity in older adult patients with traumatic hip fracture requiring surgical treatment. The authors investigated their hypothesis that the presence of aortic stenosis at the time of hip fracture surgery would be associated with an increase in mortality and serious complications. Abstract: Objectives: The majority of hip fracture patients in the United States are older adult patients with multiple comorbidities. Aortic stenosis (AS) in older adult patients with traumatic hip fracture is not uncommon. This study investigated the association between AS and postoperative mortality and serious complications. Methods: In this retrospective cohort study, a chart review was performed of patients with AS who underwent hip fracture surgical repair between January 2011 and December 2019 within one health system. A control group of hip fracture patients without AS was identified and matched based on body mass index, age, sex, date of surgery and Charlson Comorbidity Index. The primary outcome of interest was 90-day mortality; secondary outcomes included 30-day postoperative complications, intensive care unit admission (ICU), and hospital length of stay. Results: In total, 146 hip fracture patients with AS and 146 without AS were identified. In the AS group, there was an increased odds of 90-day mortality (odds ratio 2.64, 95% confidence interval 1.32–5.28, P = 0.005), and an increased odds of ICU admission (odds ratio 3.00, 95% confidence interval 1.36–6.68, P = 0.004). Conclusions: The presence of AS was independently associated with an increase in 90-day mortality and postoperative ICU stay in patients undergoing surgical repair of a hip fracture.